Size and Composition of Marek's Disease Virus Deoxyribonucleic Acid - Lee, L. F. (1971)
Deoxyribonucleic acid (DNA) extracted from purified nucleocapsids of Marek's disease herpesvirus (MDV) was cosedimented with T4 and with herpes simplex virus (HSV) DNA in neutral sucrose density gradients and with T4 DNA in alkaline sucrose density gradients. These experiments indicated that the intact MDV DNA had a sedimentation constant of 56S corresponding to a molecular weight of 1.2 × 10(8) daltons. In the alkaline gradients, the largest and most prominent band contains a DNA sedimenting at 70S corresponding to 6.0 × 10(7) daltons in molecular weight. The DNA is therefore double-stranded and not cross-linked. Isopycnic sedimentation of the MDV DNA molecules with SPO1, Micrococcus lysodeikticus, and HSV DNA gave a density of 1.705 g/cm(3) corresponding to 46 guanine plus cytosine moles per cent. Lastly, in hybridization tests the DNA hybridized with RNA of infected cells but not with that of uninfected cells supporting the conclusion that it is viral.